Investigating newman's error in integral calculus - Shida, N. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The main objective is to investigate the types of difficulties and errors faced by polytechnic students when solving integral calculus problem in Engineering Mathematics. The types of error selected in this study were motivation, understanding, transformation, process skills, coding, and negligence. The study respondents consisted of 128 Semester 2 students from Diploma in Electrical Engineering and Diploma in Mechanical Engineering at Polytechnic Ibrahim Sultan. Data analysis revealed that mostly students made errors in understanding and processing skills. The results verified that there were serious difficulties among polytechnic students in learning integral calculus through problem solving. The input from this study is expected to be a guideline for additional mathematics lectures, especially in planning and implementing better teaching so that mistakes made by students can be minimised.